Analisa Penerimaan Dan Pengelolaan Dana Nasabah Pada Bank Jateng Cabang Koordinator Magelang - May Linda Nugraheni; Chaidir Iswanaji (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
The purpose of this study was to determine the Acceptance and Management of Customer Funds at Bank Jateng, Magelang Coordinator Branch. This type of research is qualitative, because it emphasizes the process that is taken from the phenomenon and then the conclusion is drawn. The object of this research came from 20 informants or resource persons who work at the Bank Jateng, Magelang Coordinator Branch. The data source of this study came from an informant who was interviewed structurally. Based on the data analysis, it can be concluded that: (1) Receipt of customer funds at the Magelang Coordinator Branch Bank Jateng uses the accrual-based method. Where the funds received by the Magelang Coordinator Branch Bank Central Java can be in the form of demand deposits, savings deposits, and time deposits. These funds are collected from the community. (2) Management of customer funds at the Magelang Coordinator Branch Bank Central Java uses a cash-based method. The management of customer funds at Bank Jateng, the Coordinator of Magelang Branch, is in the form of loans, such as: PLO credit, Small Business Credit (KUK), Multipurpose Credit, People's Business Credit (KUR), KFW Loans, and additional business capital for family business activities.